(untitled) (Mustansiria Dental Journal, 2018)
The aim of this study was to evaluate the effect of 5.25 sodium hypochlorite and 17%EDTA on the microhardness of root canal dentin . Fifteen, maxillary incisor teeth extracted for periodontal reasons were used. The crowns of the teeth were removed at the CEJ. The roots were separated longitudinally into two segments, embedded in acrylic resin, and polished. A total of 30specimens were divided into 3 groups of 10 teeth at random according to the irrigation solution used: group 1: 5.25% NaOCl for 1min; group 2: 17% EDTA for 1 min; and group 3: distilled water (control). Each group was submitted to Vickers microhardness indentation tests. The data were recorded as Vickers numbers and the results were analyzed statistically by using one-way ANOVA. The results showed that, irrigation with either sodium hypochlorite or EDTA decreased the microhardness value of root dentin. Irrigation with EDTA gave more reduction of dentin compared to sodium hypochlorite. The reduction of VHN of dentin following the irrigation treatment was statistically significant (p< 0.05 ) . Both sodium hypochlorite and EDTA irrigation solution significantly reduced the microhardness of root dentin. .